MicroRNA Profile of Granulosa Cells after Ovarian Stimulation Differs According to Maturity of Retrieved Oocytes - Kim, Y. J. (Geburtshilfe Frauenheilkd, 2016)
Background: Recent animal studies demonstrated that regulating the microRNA (miRNA) in granulosa cells (GCs) modulates the meiotic competence of oocytes. However, the difference in expression profiles of miRNAs in human GCs according to the maturity of the oocyte still remains to be elucidated. Objective: This observational study investigated whether the miRNA profile of human GCs differs according to the maturity of the retrieved oocyte after controlled ovarian stimulation for in vitro fertilization (IVF). Methods: Ten women who underwent ovarian stimulation cycles with GnRH agonist long protocols were recruited. The follicular fluid (FF) from dominant follicles was individually aspirated at oocyte retrieval. Oocytes were divided into two groups according to oocyte maturity (“mature group” vs. “immature group”). GCs were collected from the FF and miRNA was analyzed using real-time PCR. Results: Mean number of MII oocytes in the mature group was 1.6 ± 0.9 with none in the immature group (p = 0.008). Mean number of MI oocytes was 5.6 ± 2.1 in the mature group and 1.0 ± 0.0 in the immature group (p = 0.008). The total number of retrieved oocytes was 8.8 ± 1.9 in the mature group and 2.0 ± 1.2 in the immature group (p = 0.008). The GCs of the mature group showed a significantly lower expression of hsa-let-7b compared to the GCs of the immature group (p < 0.001). Conclusion: Taken together, the miRNA expression profiles of human GCs obtained from dominant follicles are associated with maturity of the adjacent oocyte and may be useful as a prognosticator of IVF outcome.